2018
DOI: 10.1093/intimm/dxy016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms controlling nucleic acid-sensing Toll-like receptors

Abstract: Nucleic acid (NA)-sensing Toll-like receptors (TLRs) respond to DNA/RNA derived from pathogens and dead cells. Structural studies have revealed a variety of molecular mechanisms by which TLRs sense NAs. Double-stranded RNA and single-stranded DNA directly bind to TLR3 and TLR9, respectively, whereas TLR7 and TLR8 bind to nucleosides and oligoribonucleotides derived from RNAs. Activation of ligand-bound TLRs is influenced by the functional status of TLRs. Proteolytic cleavage of NA-sensing TLRs enables ligand-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 80 publications
1
86
0
Order By: Relevance
“…Other studies have also pointed out differences in signaling between different TLR7/8 ligands 78 . Human PBMCs respond to R848 and ssRNA with pro-inflammatory cytokines but only ssRNA was able to induce type I IFNs 79 and recent studies suggest ligand-induced trafficking of TLR containing endosomes dictates different responses 22,80,81 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also pointed out differences in signaling between different TLR7/8 ligands 78 . Human PBMCs respond to R848 and ssRNA with pro-inflammatory cytokines but only ssRNA was able to induce type I IFNs 79 and recent studies suggest ligand-induced trafficking of TLR containing endosomes dictates different responses 22,80,81 .…”
Section: Discussionmentioning
confidence: 99%
“…Ten functional TLRs have been discovered in humans of which TLR3, TLR7, TLR8, and TLR9 are located in endosomes and lysosomes 17 . TLR7 and TLR8 recognize single-stranded RNA (ssRNA) in the forms of degradation products, nucleosides, and oligoribonucleotides [18][19][20][21][22] while TLR3 and TLR9 bind doublestranded RNA (dsRNA) and double-stranded DNA (dsDNA), respectively 23,24 . Activated TLR dimers recruit adaptor proteins MyD88 (myeloid differentiation primary response 88) or TRIF (Toll/interleukin-1 (IL-1) receptor domain-containing adapter protein inducing interferon-β (IFN-β)) which signal through sequential activation of IRAK (IL-1 receptor-associated kinase) family kinases, IKKs (inhibitor of κB kinase), and MAPKs (mitogen-activated protein kinase), leading to the activation of the transcription factors NF-κB and AP-1-driving inflammatory cytokines, or interferon regulatory factors (IRFs) driving type I IFNs 25 .…”
mentioning
confidence: 99%
“…The Innate immune system responds to a variety of pathogens. Recognition of these products depends on pathogen sensors, which include TLRs, NOD‐like receptors (NLRs), and RIG‐I‐like receptors (RLRs) . These pathogen sensors respond to degradation products derived from pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Among TLRs, TLR‐9 recognizes unmethylated CpG dinucleotides expressed in bacteria and viruses and also vertebrate DNA. The TLRs are presented in different locations of the cells; for example, TLR‐1, TLR‐2, TLR‐4 and TLR‐5 are represented on the cell membrane surface, while TLR‐9 is intracellular and is located on the endosomal membrane for binding to its ligand . Many studies have shown that TLR‐9 expression is not limited to immune system cells.…”
Section: Introductionmentioning
confidence: 99%
“…The TLRs are presented in different locations of the cells; for example, TLR-1, TLR-2, TLR-4 and TLR-5 are represented on the cell membrane surface, while TLR-9 is intracellular and is located on the endosomal membrane for binding to its ligand. 12 Many studies have shown that TLR-9 expression is not limited to immune system cells. Expression of TLR-9 was found in various types of normal epithelial cells and also tumour cells such as gastric, brain, lung, and breast.…”
Section: Introductionmentioning
confidence: 99%